Welenrengnge Model: Formation of National Character Among Students of SMK Negeri 6 Pangkep Regency, South Sulawesi - A B. Takko Bandung; St. Nursaadah; Nasaruddin Salam (Universitas Lancang Kuning, 2023)
The erosion of national character among young generations nowadays, including the students of SMK Negeri 6 Pangkep, highlights the importance of national character strengthening training. This training focuses on strengthening MARITIME character (manly, wise, religiously innovative, tough, integrity, independent) for SMKN 6 Pangkep using the Welenrengnge Model. The method used in this training includes closing reading of training materials, lectures/presentations, in-depth discussions on MARITIME character, each participant making discussion reports, field practices, and tutorials. Field practices are conducted with a number of games to train the practice of MARITIME character. The tutorial method is used for consultation and to strengthen understanding and application of MARITIME character. The results of the training show that students realize the importance of this activity to increase knowledge, insight, national consciousness, and to stimulate creativity and innovation through games. Practice through games can build wisdom, independence, toughness, and humanity. Another important aspect is the creation of a religious atmosphere.